2014
DOI: 10.3892/etm.2014.2033
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor exerts neuroprotective actions against amyloid β-induced apoptosis in neuroblastoma cells

Abstract: Alzheimer’s disease (AD) brains demonstrate decreased levels of brain-derived neurotrophic factor (BDNF) and increased levels of β-amyloid peptide (Aβ), which is neurotoxic. The present study assessed the impact of BDNF on the toxic effects of Aβ25–35-induced apoptosis and the effects on BDNF-mediated signaling using the MTT assay, western blotting and reverse transcription quantitative polymerase chain reaction. Aβ25–35 was found to induce an apoptosis, dose-dependent effect on SH-SY5Y neuroblastoma cells, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…A number of studies have reported that the Bcl-2 family proteins participate in AD, and are associated with cell apoptosis (15,16). In particular, Bcl-2 protein is known to inhibit a variety of apoptotic pathways, and in the majority of cases, Bcl-2 is considered to function through the inhibition of Bax protein (17).…”
Section: B Amentioning
confidence: 99%
“…A number of studies have reported that the Bcl-2 family proteins participate in AD, and are associated with cell apoptosis (15,16). In particular, Bcl-2 protein is known to inhibit a variety of apoptotic pathways, and in the majority of cases, Bcl-2 is considered to function through the inhibition of Bax protein (17).…”
Section: B Amentioning
confidence: 99%
“…One of the pathological features of AD is the loss of a large number of neurons. The predominant underlying mechanism of neuronal loss resulting from AD is apoptosis, and the neuronal apoptosis hypothesis is an important aspect of AD pathogenesis (9). The neurons of the brain are particularly sensitive to apoptotic damage (10).…”
Section: Introductionmentioning
confidence: 99%
“…As a member of neurotrophic factor family, which can support the growth, survival, and differentiation of neurons, BDNF has attracted wide attention for its multipotency in diverse brain diseases, whereas its potential regulatory role in ropivacaine-induced neuronal injury was not explored and consequently became the focus of our research [19,20].To further verify the regulatory role of BDNF in this pathological procedure, the ropivacaine-damaged cells were treated with BDNF, showing that under the protection of BDNF, the morphological damages presented by synapse disappearance and cell atrophy were significantly reversed, which preliminarily indicates its protective role in ropivacaine-induced neuronal injury at the cytological level. Similar phenomena have also been observed in various related studies [21].…”
Section: Discussionmentioning
confidence: 99%